Urban Green Areas: Examining Honeybee Pathogen Spillover in Wild Bees Through Shared Foraging Niches - Sorvillo, Carla; Malabusini, Serena; Holzer, Erica; Frasnelli, Matteo; Giovanetti, Manuela; Lavazza, Antonio; Lupi, Daniela (Applied sciences, 2025)
In urbanized environments, the expansion of urban areas has led to the creation of fragmented green spaces such as gardens and parks. While these areas provide essential habitats for pollinators, they may also inadvertently concentrate specimens of different species, increasing opportunities for pathogen transmission. This study highlights the importance of investigating pathogen dynamics in urban ecosystems, focusing on managed pollinators, such as Apis mellifera Linnaeus, 1758, and their wild counterparts. Over a two-year monitoring period in Milan, Italy, we examined the interactions between pollinator populations in urban green spaces and the spillover of honeybee pathogens. Our findings confirm widespread RNA virus transmission between honeybees and wild pollinators, supporting the previous studies. Notably, the Acute Bee Paralysis Virus (ABPV) exhibited the highest prevalence across both sampling years, underscoring its significant role in pathogen dynamics. These results emphasize the need for regular research to mitigate pathogen spillover risks in urban pollinator communities and inform conservation strategies.